The Impact of the Covid-19 Pandemic on the Feasibility of the Laying Hens Business in Sumberejo Village, Blitar Regency, East Java Province, Indonesia - Ngabdus Sholihin; Nining Haryuni; Lestariningsih Lestariningsih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
This research was conducted to determine the impact of Covid-19 on the feasibility of laying hens in Sumberjo Village. This research was conducted using a descriptive quantitative approach. Quantitative approach is research that uses data in the form of numbers. The description is carried out from the results of statistical analysis of the data collected during the study. Respondents in this study were determined by purposive sampling on laying hens in Sumberjo Village. The number of respondents used in this study was calculated by the slovin formula. Data collection in this study was carried out through observation and surveys using questionnaires. The results showed that the total cost of each 5000 laying hens was Rp. 120.5600.00/month; total revenue of Rp. 109,411,764.71/month; income of Rp. -11,148,235.29 and the R/C value is 0.91. The results of this study narrowed down to one conclusion that the Covid-19 pandemic had an impact on the low feasibility of producing chicken business.